Is voting really habit-forming and transformative? Long-run effects of earlier eligibility on turnout and political involvement from the UK - Jonas Jessen; Daniel Kühnle; Markus Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Habit formation theory and the transformative voting hypothesis both imply that voting has downstream consequences for turnout and political involvement. Although several studies have applied causal research designs to study this question, the long-run evidence is extremely limited, especially for potentially transformative effects. We jointly examine the short- and long-term impact of earlier voting eligibility on subsequent turnout and political involvement using rich panel data from the UK. Exploiting the eligibility cut-off for national elections within a regression discontinuity design, our precise estimates document a short-run increase in voting - for those able to vote earlier - alongside a contemporaneous increase in several measures of political involvement. However, we show that these short-term effects fade away quickly and do not translate into permanent changes in turnout propensity or political involvement. Our results imply that, in a setting with low institutional barriers to vote, the transformative effects of voting are short-lived at most.
Keywords: D01; D70; D72; 330; habit formation; transformative voting hypothesis; voter turnout; political involvement; regression discontinuity